Pengaruh Kepemilikan Keluarga dan Good Corporate Governance Terhadap Kualitas Laba dan Kinerja Perusahaan - Mathova, Anna; Perdana, Halim Dedy; Rahmawati, Isna Putri (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
This research is purposed to find out the effect of family ownership and Good Corporate Governance toward the earning quality and firm performance of the company listed in Indonesian Stock Exchange from 2012 up to 2014. The sample of this research is using 153 companies for the earning quality model and 137 companies for firm performance model in Indonesia from 2012 up to 2014. The sampling is done using purposive sampling method. The analysis method used is multiple linear regression analysis method using SPSS version 21.00. The result of the regression testing of earning quality model shows that only debt ratio influent the earning quality, while family ownership, institutional ownership, independent commissioner, type audit and payout ratio do not. The test for the firm performance shows that the institutional ownership, independent commissioner, type audit and payout ratio are influencing the firm performance while the family ownership and debt ratio are not.